Improving Students' Interest in Mathematics Learning through Problem-Based Learning with Worked Examples and Interactive Quizzes on SPLDV - Riza Nur Fadila; Ali Mahmudi; Raden Rosnawati (Jurnal Inovasi Matematika, 2026)
Low student interest in SPLDV remains a challenge in mathematics education, primarily due to the limited integration of ICT-based learning media, inadequate learning resources, and the predominance of conventional teaching approaches that minimize active student participation. This study aims to examine how the PBL model, supported by worked examples and interactive quizzes, enhances students' learning interest in SPLDV instruction. Employing a classroom action Research design, the study involved 31 eighth-grade students from one of MTs Negeri in Bantul during the 2024/2025 academic year. Data were collected using questionnaires and observation sheets measuring students’ learning interest. Descriptive statistical analysis was conducted to determine the percentage increase in learning interest across cycles, both overall and for each indicator. The findings reveal a significant improvement in students’ learning interest following the implementation of the PBL model supported by worked examples and interactive quizzes. This increase is derived from the average scores for learning interest, observation sheets, and positive student responses. Students demonstrated greater enthusiasm, attention, motivation, and improved learning outcomes. These results suggest that integrating interactive digital components and structured worked examples within the PBL framework provides an effective pedagogical innovation to foster students' mathematics learning interest and learning outcomes.